Device classification based data encryption for internet of things. (28th September 2020) - ,; Sharma, T.P.
The internet of things (IoT) has gained much popularity and has become an essential topic of research, because of its vast implementations. It has emerged as a field of great potential, impact, and growth. Despite its privacy concerns and security issues, it still is growing in demand for large-scale deployment. In this paper, we propose class-specific data encryption techniques for heterogeneous IoT devices. Devices are classified based on their computational and communication capabilities. Accordingly, different schemes for data encryption/decryption are proposed at different levels of interconnection across devices of different classes. The classification makes it easy to develop, study, and analyse the behaviour of the devices, as the devices of the same class have similar properties and performance. It also helps to develop standards of security protocols, policies, and frameworks based on the device class. Simulation experiments reveal significant improvements in the solution of encryption techniques for given scenarios.